Clinical and Epidemiological Characteristics of 30 Fatal Cases of Crimean-Congo Hemorrhagic Fever in Kabul, Afghanistan: A Retrospective Observational Study - Rasikh AS; Aram MM; Noory AT (Infection and Drug Resistance, 2023)
Ahmad Shekaib Rasikh,1 Mohammad Maroof Aram,2 Abdul Tawab Noory1 1Department of Infectious Diseases, Ali Abad Teaching Hospital, Kabul University of Medical Sciences, Kabul, Afghanistan; 2Department of Internal Medicine, Ali Abad Teaching Hospital, Kabul University of Medical Sciences, Kabul, AfghanistanCorrespondence: Ahmad Shekaib Rasikh, Tel +93 791906514, Email shekaib.rasikh@gmail.comObjective: Crimean-Congo hemorrhagic fever (CCHF) is a zoonotic disease associated with a high fatality rate. CCHF is endemic in Afghanistan, and its morbidity and mortality have increased recently but there is limited data about the characteristics of fatal cases. We aimed to report the clinical and epidemiological features of fatal CCHF cases who were admitted to Kabul Referral Infectious Diseases (Antani) Hospital.Methods: This is a retrospective cross-sectional study. The demographic and presenting clinical and laboratory features of 30 fatal CCHF cases diagnosed by reverse transcription polymerase chain reaction (RT-PCR) or enzyme-linked immunosorbent assay (ELISA) tests were collected from the patients’ records between March 2021 and March 2023.Results: During the study period, a total of 118 laboratory-confirmed CCHF patients were admitted to Kabul Antani Hospital of whom 30 patients (25 males, 5 females) consequently died, indicating a 25.4% case fatality rate (CFR). The age of the fatal cases ranged from 15 to 62 years and their mean age was 36.6 ± 11.7 years. Concerning occupation, the patients were butchers (23.3%), animal dealers (20%), shepherds (16.6%), housewives (16.6%), farmers (10%), student (3.3%), and others (10%). The clinical symptoms of the patients on admission were fever (100%), generalized body pain (100%), fatigue (90%), bleeding (any type) (86.6%), headache (80%), nausea/vomiting (73.3%), and diarrhea (70%). The initial abnormal laboratory findings were leukopenia (80%), leukocytosis (6.6%), anemia (73.3%), and thrombocytopenia (100%), raised hepatic enzymes (ALT & AST) (96.6%) and prolonged prothrombin time/international normalized ratio (PT/INR) (100%).Conclusion: The hemorrhagic manifestations associated with low platelet and raised PT/INR levels are linked with fatal outcomes. A high index of clinical suspicion is required to recognize the disease at an early stage and to begin the treatment promptly for reducing mortality.Keywords: Afghanistan, Crimean-Congo hemorrhagic fever, fatal, thrombocytopenia